2023
DOI: 10.1002/bit.28407
|View full text |Cite
|
Sign up to set email alerts
|

Effect of protein fouling on filtrate flux and virus breakthrough behaviors during virus filtration process

Abstract: Virus filtration process is used to ensure viral safety in the biopharmaceutical downstream processes with high virus removal capacity (i.e., >4 log10). However, it is still constrained by protein fouling, which results in reduced filtration capacity and possible virus breakthrough. This study investigated the effects of protein fouling on filtrate flux and virus breakthrough using commercial membranes that had different symmetricity, nominal pore size, and pore size gradients. Flux decay tendency due to prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 36 publications
(51 reference statements)
1
2
0
Order By: Relevance
“…The LRV profile for this pre-soaked membrane was nearly identical to that seen for the clean membrane, consistent with the very small change in permeability (<5%) associated with the hIgG adsorption. Similar results were obtained by Suh et al (2023a) using dual-layer Pegasus TM SV4 membranes exposed to a BSA solution, with the retention characteristics evaluated using the bacteriophage MS2. Thus, protein adsorption (in the absence of filtration) does not appear to cause a significant change in virus retention for the Pegasus TM SV4 membrane, although this may simply be due to the relatively low amount of hIgG adsorption seen after pre-soaking the membrane in the protein solution.…”
Section: Virus Retention Behaviorsupporting
confidence: 81%
See 1 more Smart Citation
“…The LRV profile for this pre-soaked membrane was nearly identical to that seen for the clean membrane, consistent with the very small change in permeability (<5%) associated with the hIgG adsorption. Similar results were obtained by Suh et al (2023a) using dual-layer Pegasus TM SV4 membranes exposed to a BSA solution, with the retention characteristics evaluated using the bacteriophage MS2. Thus, protein adsorption (in the absence of filtration) does not appear to cause a significant change in virus retention for the Pegasus TM SV4 membrane, although this may simply be due to the relatively low amount of hIgG adsorption seen after pre-soaking the membrane in the protein solution.…”
Section: Virus Retention Behaviorsupporting
confidence: 81%
“…Leisi et al (2022) found no effect of hIgG on the retention of minute virus of mice (MVM) by the Planova TM 20 N, but there was a significant decline in virus retention with increasing volumetric throughput for the Pegasus TM SV4 when filtering MVM spiked into a 10 g/L hIgG solution. Suh et al (2023a) The objective of this study was to obtain a more detailed understanding of the effects of proteins on virus retention by the Pegasus TM SV4 membrane. Data were obtained using a single layer of this dual-layer filter since virus retention by the dual-layer filter is typically beyond the limit of detection.…”
Section: Introductionmentioning
confidence: 99%
“…Here the aim is to validate the removal of contaminating virus particles while purifying the protein product. Membrane-based filtration processes effectively remove viruses from protein solutions, ensuring the production of safe and high-quality biotherapeutics. , Moreover, membranes are integral to viral vector concentration through diafiltration processes. By selectively allowing the passage of water and small solutes while retaining viral vectors, these membranes enable the concentration of viral vectors, enhancing the overall efficiency of downstream processing .…”
Section: Introductionmentioning
confidence: 99%